Dietary Mannan‐oligosaccharides potentiate the beneficial effects of Bifidobacterium bifidum in broiler chicken. (1st November 2020) - Dev, Kapil; Akbar Mir, Nasir; Biswas, Avishek; Kannoujia, Jyoti; Begum, Jubeda; Kant, Rajiv
Abstract: This study investigated the effects of dietary Bifidobacterium bifidum (BFD) and mannan‐oligosaccharide (MOS), as a synbiotic, on the production performance, gut microbiology, serum biochemistry, antioxidant profile and health indices of broiler chicken. Six dietary treatments were T1 (negative control), T2 (positive control‐20 mg antibiotic BMD kg −1 diet; BMD: bacitracin methylene disalicylate), T3 (0·1% MOS + 10 6 CFU BFD per g feed), T4 (0·1% MOS + 10 7 CFU BFD per g feed), T5 (0·2% MOS + 10 6 CFU BFD per g feed) and T6 (0·2% MOS + 10 7 CFU BFD per g feed). Significantly ( P < 0·01) better growth performance and efficiency was observed in birds supplemented with 0·2% MOS along with 10 6 CFU BFD per g of feed compared to BMD and control birds. Supplementation with 0·2% MOS along with either 10 6 or 10 7 CFU BFD per g feed reduced ( P < 0·01) the gut coliform, Escherichia coli, total plate count, and Clostridium perfringens count and increased the Lactobacillus and Bifidobacterium count. Significantly ( P < 0·01) higher serum and liver antioxidant enzyme pool, serum HDL cholesterol and lower serum glucose, triglyceride, total cholesterol, cardiac risk ratio, atherogenic coefficient and atherogenic index of plasma were observed in birds supplemented with 0·2% MOS along with 10 6 CFU BFD per g of feed compared to control or BMD supplemented birds. Better production performance, gut microbial composition, serum biochemistry, antioxidant profile and health indices were depicted by broiler chicken supplemented with 0·2% MOS and 10 6 CFU BFD per g of feed.